The influence of product quality, brand image, and price on consumers’ purchase intention toward acer laptops in Batam city - Fransiska Weny Sinaga; Alice Erni Husein (International Journal of Applied Finance and Business Studies, 2025)
This study investigates the influence of product quality, brand image, and price on consumer purchase intention toward Acer laptop products marketed by PT X in Batam City. Employing a quantitative descriptive approach, data were collected from 100 respondents through an online questionnaire and analyzed using multiple linear regression in SPSS. The results demonstrate that all three independent variables, product quality, brand image, and price, have a simultaneous and significant effect on purchase intention. Individually, brand image (β = 0.477, Sig. = 0.000) emerged as the most dominant factor influencing consumers’ decisions, followed by price (β = 0.436, Sig. = 0.000), while product quality, though statistically significant (β = 0.011, Sig. = 0.025), exhibited the smallest effect. These findings suggest that consumers in Batam prioritize psychological and symbolic brand perceptions, as well as perceived value-for-money considerations, over purely functional attributes when purchasing laptops. The managerial implications highlight the need for PT X to focus on strengthening brand image through reputation-building and superior after-sales service, implementing competitive yet value-reflective pricing strategies, and maintaining consistent product quality assurance. Overall, the study provides empirical evidence that branding and perceived price fairness are key determinants of purchase intention in the technology retail market.